CircNFIX promotes progression of glioma through regulating miR-378e/RPN2 axis - Chenyu Ding; Zanyi Wu; Honghai You; Hongliang Ge; Shufa Zheng; Yuanxiang Lin; Xiyue Wu; Zhangya Lin; Dezhi Kang (Journal of Experimental & Clinical Cancer Research, 2019)
Abstract Background Circular RNA nuclear factor I X (circNFIX) has been reported to play an important role in glioma progression. However, the mechanism by which circNFIX participates in glioma progression remains poorly understood. Methods GERIA online were used to analyze the abnormally expressed genes in glioma tissues. The expression levels of circNFIX, microRNA (miR)-378e and Ribophorin-II (RPN2) were measured by quantitative real-time polymerase chain reaction or western blot. Cell cycle distribution, apoptosis, glycolysis, migration and invasion were determined by flow cytometry, special kit and trans-well assays, respectively. The target association between miR-378e and circNFIX or RPN2 was confirmed by luciferase reporter assay, RNA immunoprecipitation and pull-down. Xenograft model was established to investigate the role of circNFIX in vivo. Results The expression of circNFIX was enhanced in glioma tissues and cells compared with matched controls and high expression of circNFIX indicated poor outcomes of patients. Knockdown of circNFIX led to arrest of cell cycle, inhibition of glycolysis, migration and invasion and promotion of apoptosis in glioma cells. circNFIX was a sponge of miR-378e. miR-378e overexpression suppressed cell cycle process, glycolysis, migration and invasion but promoted apoptosis. miR-378e silence abated the suppressive role of circNFIX knockdown in glioma progression. RPN2 as a target of miR-378e was positively regulated via circNFIX by competitively sponging miR-378e. Silencing circNFIX decreased glioma xenograft tumor growth by regulating miR-378e/RPN2 axis. Conclusion Knockdown of circNFIX inhibits progression of glioma in vitro and in vivo by increasing miR-378e and decreasing RPN2, providing a novel mechanism for understanding the pathogenesis of glioma.